What is the answer to 3S - 3 =0 ? Is it S?  

Expert Answers
jgeertz eNotes educator| Certified Educator

`3S-3=0`

Add `3` to both sides of the equation.

`3S=3`

Divide both sides by `3` .

`(3S)/3 = 3/3`

`S=1`

(S cannot be the answer since it is the variable you are solving for.)

S=1

 

atyourservice | Student

3S - 3 =0   add 3 to both sides

3s-3+3=0+3

`3s=3 `   divide by 3     `(3s)/3 = 3/3`    s=1

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question